Bacterial Contamination of Clothes and Environmental Items in a Third-Level Hospital in Colombia - J. C. Cataño; L. M. Echeverri; C. Szela (Interdisciplinary Perspectives on Infectious Diseases)
Objective. This study evaluates the bacterial contamination rate of items in the hospital setting that are in frequent contact with patients and/or physicians. By determining the bacterial species and the associated antibiotic resistance that patients are exposed to. Methods. Hospital-based cross-sectional surveillance study of potential bacterial reservoirs. Cultures from 30 computer keyboards, 32 curtains, 40 cell phones, 35 white coats, and 22 ties were obtained. Setting. The study was conducted an urban academic 650-bed teaching hospital providing tertiary care to the city of Medellin, Colombia. Results. In total, 235 bacterial isolates were obtained from 159 surfaces sampled. 98.7% of the surfaces grew positive bacterial cultures with some interesting resistance profiles. Conclusion. There are significant opportunities to reduce patient exposure to frequently pathogenic bacteria in the hospital setting; patients are likely exposed to many bacteria through direct contact with white coats, curtains, and ties. They may be exposed to additional bacterial reservoirs indirectly through the hands of clinicians, using computer keyboards and cell phones.